2020
DOI: 10.1016/j.wroa.2020.100065
|View full text |Cite
|
Sign up to set email alerts
|

The role of mobile genetic elements in organic micropollutant degradation during biological wastewater treatment

Abstract: Wastewater treatment plants (WWTPs) are crucial for producing clean effluents from polluting sources such as hospitals, industries, and municipalities. In recent decades, many new organic compounds have ended up in surface waters in concentrations that, while very low, cause (chronic) toxicity to countless organisms. These organic micropollutants (OMPs) are usually quite recalcitrant and not sufficiently removed during wastewater treatment. Microbial degradation plays a pivotal role in OMP conversion. Microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 170 publications
(262 reference statements)
0
25
0
Order By: Relevance
“…The biomass density in the bioreactor presented in this study was ten times lower than a common WWTP activated sludge reactor. As conjugation events are more likely to happen at higher densities or in environments where cells are in close contact such as granules and biofilms (Rios‐Miguel et al ., 2020), this experiment might underestimate the true role that MGEs play in the degradation of pharmaceutical micropollutants. Furthermore, previous studies reported higher relative abundances of MGEs in sites with higher OMP exposure over much longer periods of time (years) compared with our bioreactor experiment that lasted 2.5 months (Dunon et al ., 2013; Dealtry et al ., 2014).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The biomass density in the bioreactor presented in this study was ten times lower than a common WWTP activated sludge reactor. As conjugation events are more likely to happen at higher densities or in environments where cells are in close contact such as granules and biofilms (Rios‐Miguel et al ., 2020), this experiment might underestimate the true role that MGEs play in the degradation of pharmaceutical micropollutants. Furthermore, previous studies reported higher relative abundances of MGEs in sites with higher OMP exposure over much longer periods of time (years) compared with our bioreactor experiment that lasted 2.5 months (Dunon et al ., 2013; Dealtry et al ., 2014).…”
Section: Resultsmentioning
confidence: 94%
“…Mobile genetic elements (MGEs) have been previously suggested to be involved in microbial adaptation. MGEs may thus play a role in the biodegradation of xenobiotics or organic micropollutants in different environments such as soils and WWTPs (Top and Springael, 2003; Rios‐Miguel et al ., 2020). Furthermore, previous studies found a correlation between pesticide exposure and MGE abundance in soils and agricultural WWTPs (Dunon et al ., 2013; Dealtry et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our strain, Pfast, also had two insertion sequences (IS6100 and IS21, OACKLNDA_05756, OACKLNDA_05781), one Tn3 transposase gene (OACKLNDA_05752), and one recombinase gene (OACKLNDA_05755) near the highly-expressed amidase gene. Consequently, the whole gene cluster might have been exchanged between different species via horizontal gene transfer (HGT) (Rios Miguel et al, 2020). Finally, the low number of homologous proteins in the NCBI database might indicate the recent evolution of this amidase towards paracetamol biodegradation or our limited ability to find and identify these genes.…”
Section: Highly-expressed Amidases In the Two Pseudomonas Spp Isolatesmentioning
confidence: 99%
“…The biomass density in the bioreactor presented in this study was ten times lower than a common WWTP activated sludge reactor. As conjugation events are more likely to happen at higher densities or in environments where cells are in close contact such as granules and biofilms (Rios-Miguel et al, 2020), this experiment might underestimate the true role that MGEs play in the degradation of pharmaceutical micropollutants. Furthermore, previous studies reported higher relative abundances of MGEs in sites with higher OMP exposure over much longer periods of time (years) compared to our bioreactor experiment that lasted 2.5 months (Dealtry et al, 2014;Dunon et al, 2013).…”
Section: Mobile Genetic Elements Relative Abundancementioning
confidence: 99%
“…Mobile genetic elements (MGEs) have been previously suggested to be involved in microbial adaptation. MGEs may thus have played a role in the biodegradation of xenobiotics or organic micropollutants in different environments such as soils and WWTPs (Rios-Miguel et al, 2020;Top and Springael, 2003). Furthermore, previous studies found a correlation between pesticide exposure and MGE abundance in soils and agricultural WWTPs (Dealtry et al, 2014;Dunon et al, 2013).…”
Section: Introductionmentioning
confidence: 95%